O alcoolismo e o alcoolista no capitalismo : a psicologia histórico-cultural na defesa da historicidade para o enfrentamento do problema - Moraes, Renata Jacintho Siqueira de (2011)
This dissertation consists of some bibliographical research carried out in the Postgraduate Program in Psychology at the State University of Maringá (2010-2011) in the research field of Constitution of the Subject and Historicity. It aimed at both investigating the theoretical and methodological contributions offered by the historical-cultural psychology and the historicaldialectical materialism to understand alcoholism and the alcoholic in the capitalist society as well as establishing some possible ways for the psychologist to cope with it. Current hegemonic discourses about alcoholism were examined in order to identify the main assumptions related to etiology, diagnostic instruments and methods of treatment. For that, the historical course of man?s relationship with alcohol was regained by considering the means of production and consumption of life (primitivism, classic ancients, feudalism and capitalism) and production and consumption of alcohol in each society. This way, it was possible to understand the historicity of human facts, in particular, the constitution of alcohol as a commodity and alcoholism as a pathology. Deepening knowledge of alcoholism in the capitalist production means as well as of psychological conceptions and the psychologist's work in this context brought back the Brazilian history in the early 20th century, regarding psychiatric and psychological theories and practices towards alcoholism. Current scientific papers on alcoholism were related to the life and work conditions of Brazilian workers in that time. The theoretical and methodological foregrounding adopted for our research analysis was aimed at overcoming current psychological science assumptions and interventions to cope with alcoholism. A study of L. S. Vygotsky's work and other scholars' of historical-cultural psychology; Soviet psychiatry on alcoholism; scientific papers on the material conditions of ancient URSS which constituted the present setting of psychology; scientific papers on alcoholism and collective health today, was thoroughly conducted. It was verified that the society that attempted to overcome the private property from means of production as well as the existing social classes faced the alcoholism matter as well. Some elements of comparison between the actions taken in order to cope with alcoholism in the Capitalist West, especially, in Brazil, and those taken in the URSS, the advancement and contradictions in the Soviet society. As a result, some assumptions can be assumed by considering Vygotsky's theory, especially, his works on defectology and some of his partners' and followers', and the Marxist Collective Health formulations. They confirm that the conception of subject and his or her psyche is a synthesis of multiple determinations understood in its whole. In conclusion, we were aware of the importance of history as a theoretical and methodological tool for a progress in psychological science studies so as neither individualize nor naturalize man, his or her psyche, behavior and sickness from alcoholism. Therefore, the present study itself followed the domains of its own behavior in an effort to cope with alcoholism and material, economic and social objective conditions brought by alienation, split between subject and society, and the resulting human sickness.